A slender red species of Entoloma (Entolomataceae) from China - Xing, Jia-Hui; He, Xin-Sheng; Li, Tai-Hui; Li, Chuan-Hua; He, Xiao-Lan (Phytotaxa, 2021)
A new species, Entoloma coccineum, is described from Sichuan Province of China. It is characterized by brilliant red, small and slender basidiomata with deeply decurrent lamellae, and cuboid basidiospores 7–11 μm. The combination of these morphological characters is very distinctive among the known taxa of Entoloma, and the molecular data of the internal transcribed spacer (ITS) and the nuclear ribosomal large subunit (nrLSU) sequences also show it to be an independent taxon. In this paper, the new species is morphologically described and illustrated in detail, phenotypic and phylogenetic closely related taxa are compared, and a phylogenetic tree based on the nrLSU sequences is presented.